Petualangan Si Tole - Meningkatkan Moderasi dan Toleransi Beragama Melalui Game Roblox Berbasis Peta Yogyakarta - Muwaffaqoh Zayiddah Ramadhania; Vincent Ariya Saccani; Akhmad Bagus Nuryanto (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Indonesia is a country rich in culture and religion. However, in the era of technological advancement, cases of intolerance and a lack of understanding of religious moderation are still often encountered, especially among the younger generation. This situation calls for engaging learning media. One innovation that can be developed to enhance understanding of religious moderation is by creating the educational game “Si Tole's Adventure.” The game is designed using the Roblox platform based on a map of Yogyakarta, which is rich in cultural diversity. This study aims to develop the game “Si Tole's Adventure” as a learning medium to improve religious tolerance. The research methods include testing the material and storyline, evaluating the game’s feasibility, conducting bug tests, and assessing the game's effectiveness. The validation results showed a very good media feasibility level (91%) for the material and very good (88%) for the questions. Effectiveness tests showed that students' understanding of religious moderation increased by 67% at the high school level and 68% at the junior high school level. In addition, observations showed a decrease in intolerant behavior and an increase in mutual respect among students. With these results, "The Adventures of Si Tole" has proven to be effective as an interactive learning medium capable of instilling the value of tolerance towards religious diversity among students.